Two-Scale Thermomechanical Simulation of Hot Stamping - Neumann, Rudolf (Schriftenreihe Kontinuumsmechanik im Maschinenbau / Karlsruher Institut für Technologie, Institut für Technische Mechanik - Bereich Kontinuumsmechanik, 2017)
Hot stamping is a hot drawing process which takes advantage of the polymorphic steel behavior to produce parts with a good strength-to-weight ratio. For the simulation of the hot stamping process, a nonlinear two-scale thermomechanical model is suggested and implemented into the FE tool ABAQUS. Phase transformation and transformation induced plasticity effects are taken into account. The simulation results regarding the final shape and residual stresses are compared to experimental findings.